2-(3′-Indolyl)-N-arylthiazole-4-carboxamides: Synthesis and evaluation of antibacterial and anticancer activities. Issue 19 (1st October 2015) - Tantak, Mukund P.; Wang, Jing; Singh, Rajnish Prakash; Kumar, Anil; Shah, Kavita; Kumar, Dalip
Graphical abstract